Perspective Hardening Technologies Are Based on Laser Surface Hardening and Self-propagating High-temperature Synthesis - Zhiguts Yurij; Kudlotyák Csaba; Pallay Dezső; Zsiguc György; Жигуц Юрій; Кудлотяк Чаба; Поллої Дезидер (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-„RIK-U” Kft., 2018)
A cikk a kombináltanyag-feldolgozás hatásának tanulmányozására irányul, amely ötvözi az önterülős magashőmérsékletű szintézis és a lézeres felületi keményedést. A szerzők elvégezték a szintézisreakciót és kiszámították az adiabatikus hőmérsékletét. Ezenkívül a szerzők egy kombinált kezelés után fedezték fel az acél mikrostruktúráját, amely klasszikus szénacél (bázis) és különböző típusú karbidokból áll. Egy külön kutatás felfedezte a fázisok tulajdonságait és a felszíni anyag mikrokeménységét, valamint a szintetizált ötvözettek lehetséges alkalmazását.

Abstract. The article is devoted to the study of the influence of combined surface material processing, which combines self-propagating high-temperature synthesis and laser surface hardening. The authors carried out theoretical calculations of the adiabatic temperature of the synthesis reaction. In addition, the authors discovered the microstructure of steel after a combined treatment, which consists of classical carbon steel (base) and carbides of various types. A separate study revealed the properties of phases and the microhardness of the surface material and the possible applications of synthesized alloys.
https://kmf.uz.ua/wp-content/uploads/2021/02/limes-2018_tom-v_v-evfolyam.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008404
Keywords: hardening technologies; high temperature synthesis